A heart of crimson flames - Mulford, A. K. (Mulford, A. K. Golden court, 2025)
"Briar Marriel, once the heir of the Golden Court, is now a prisoner in the heart of enemy territory. But when her ex-lover Maez--now a dark sorceress--comes to "rescue" her, Briar must decide if she's willing to trust the twisted version of the woman she once loved or remain under the rule of the cruel King Nero. In a war where enemies wear familiar faces, escape might come at a terrible cost. But if she can harness Maez's newfound magic, could it mean winning the war? Meanwhile, Sadie with the help of Navin races to harness ancient magic that could turn the tide of the war. With their dragon at their side, the Songkeepers uncover long-buried secrets that could save their people--or destroy them all. At the Golden Court, Queen Calla faces an impossible choice: prepare for the looming battle or risk everything to rescue their twin sister Briar. With alliances crumbling and betrayal lurking at every corner, Calla must rally their court and lead their people into war, knowing the price of failure is unthinkable. As war ravages the land, and love is tested by darkness, Briar, Sadie, and Calla must confront their pasts and find the strength to reclaim their future. In this epic conclusion to the Golden Court Trilogy, the battle for freedom--and for love--has never been more harrowing." -- Book Jacket